Desde las estructuras vitalicias a las temporales: Una aproximación a la reforma de las pensiones de supervivencia en Espa\~na; From lifetime benefits to temporary payments: An approach to survivors benefits reform in Spain - Daniel Hernández González; José Enrique Devesa Carpio (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– This article explores the possibility of transition from lifetime benefits to temporary payments, specifying the debate in the Spanish Social Security. The theoretical approach is presented and, according to the Continuous Sample of Working Lives, the application of actuarial equivalence and a sensitivity analysis on the main hypothesis, practical results are calculated. As it would be intuitively expected, the transition from lifetime benefits to temporary payments leads to better fairness in the model and a cost reduction in the initial expenses per generation for public protection system, although other perspectives, including reduced expectations for potential beneficiaries, should be also seen. Furthermore, the possibility of using different periods and amounts in the structure of expenses is shown as well. This option improves the protection at the time closest to the fact that generates the benefit.
Keywords: C10; H55; 330; Social Security; survivors benefits; lifetime and temporary income; actuarial equivalence